PENTINGNYA TEORI PERTUKARAN SOSIAL PETER M. BLAU DI ERA MASYARAKAT 5.0 - Rifqi Khairul Anam (SOCIAL EDU: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Peter M. Blau's social exchange theory remains strikingly relevant for understanding social interactions in Society 5.0, a digitally driven era where core concepts like rewards, costs, profit, and power are amplified and redefined online. This analysis demonstrates the theory's enduring power to illuminate digital phenomena such as e-commerce, the sharing economy, online labor markets, and social media dynamics, revealing user motivations and platform behaviors through an economic lens. While requiring adaptations to incorporate algorithmic mediation, expanded digital resources, and ethical concerns inherent in hyper-connected digital exchanges, Blau's framework provides a vital and insightful lens for navigating both the opportunities and challenges of social life in Society 5.0, offering a robust foundation for analyzing the complex interplay of social and economic forces shaping this new societal paradigm.